Marital Rape Regulation Issue Perspective Abu Zahra: Regulasi Marital Rape Perspektif Maslahah Abu Zahra - Fauzan, Mohamad; Ulya, Zakiyatul (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2024)
Regulation of Rape in marriage has reaped pros and cons in its implementation because it is considered contrary to religious values ​​that live in society. This paper aims to examine the regulation of rape in marriage in Indonesia and its suitability to the perspective of Abu Zahra's maslahah. The type of research is a literature review (library research) with a qualitative approach. The results of the study show 3 regulations that regulate rape in marriage in Indonesia, namely the PKDRT Law, the TPKS Law, and the Law on the Criminal Code. The 3 laws are relevant to Abu Zahra's maslahah based on 3 indicators, namely: a.) in terms of quality, the presence of this regulation is a form of darar prevention of a marriage that has the concept of mu'asyarah bi al-ma'ruf, b.) in terms of quantity, the benefits generated from this regulation will be felt by most people, especially victims of domestic violence and law enforcers, c.) from a certain period of time, the benefits of this regulation will provide long-term effects, for example as enforcement of human rights and increasing public security.